The Effect of Glutathione (GSH) Supplementation in A Dilution Medium on The Quality of Saanen Goat Semen Stored at 5°C - CHOTIMAH, QUSNUL (Livestock and Animal Research, 2025)
Objective: This study investigated the effect of Glutathione (GSH) supplementation in a dilution medium on the quality of Saanen goat semen stored at 5°C.Methods: Semen samples were collected from 1.5-year-old Saanen goats twice weekly using an artificial vagina. Samples with motility >70% were diluted in egg yolk citrate extender and divided into four treatment groups: a control (0 mM GSH), and treatments with 1 mM, 3 mM, and 5 mM GSH in 1 mL egg yolk citrate. Diluted samples were stored at 5°C for 0, 24, 48, and 72 hours. The main variables assessed were motility, viability, and abnormality of the sperm. Data were analyzed using a 4x4 factorial ANOVA, with significant differences tested by DMRT at α = 0.05.Results: Results showed that Glutathione supplementation significantly improved sperm motility and viability (p˂0.05), although no significant effects were observed on sperm abnormalities (p˃0.05). Mean sperm motility (%) and viability (%) at 0 mM, 1 mM, 3 mM, and 5 mM GSH levels were recorded as 64.61±13.65 and 83.87±8.44; 69.93±13.57 and 88.00±5.40; 72.64±13.26 and 88.57±4.75; and 72.25±13.12 and 86.07±5.69, respectively. The storage time also significantly affected sperm motility and viability (p˂0.05), with Mean s for motility (%) and viability (%) at 0, 24, 48, and 72 hours of 82.07±8.78 and 91.27±3.34; 75.25±7.63 and 87.09±5.31; 66.93±8.7 and 84.80±6.37; and 55.17±11.52 and 83.35±9.20, respectively. No significant interaction was observed between Glutathione concentration and storage duration.